2016
DOI: 10.1002/pssc.201510214
|View full text |Cite
|
Sign up to set email alerts
|

Properties of two‐dimensional electron gas in AlGaN/GaN HEMT structures determined by cavity‐enhanced THz optical Hall effect

Abstract: In this work we employ terahertz (THz) ellipsometry to determine two‐dimensional electron gas (2DEG) density, mobility and effective mass in AlGaN/GaN high electron mobility transistor structures grown on 4H‐SiC substrates. The effect of the GaN interface exposure to low‐flow‐rate trimethylaluminum (TMA) on the 2DEG properties is studied. The 2DEG effective mass and sheet density are determined tobe in the range of 0.30‐0.32m0 and 4.3‐5.5×1012 cm–2, respectively. The 2DEG effective mass parameters are found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…The 2DEG effective mass parameter is somewhat higher than the bulk GaN electron mass of 0.232m 0 [63], which is in agreement with previous reports [55,59,64]. The observed difference could be attributed to a penetration of the 2DEG wavefunction into the AlGaN barrier layer that was shown to be strongly affected by temperature [55] and it is further discussed in Ref.…”
Section: Terahertz Optical Hall Effect (Thz-ohe)supporting
confidence: 90%
See 2 more Smart Citations
“…The 2DEG effective mass parameter is somewhat higher than the bulk GaN electron mass of 0.232m 0 [63], which is in agreement with previous reports [55,59,64]. The observed difference could be attributed to a penetration of the 2DEG wavefunction into the AlGaN barrier layer that was shown to be strongly affected by temperature [55] and it is further discussed in Ref.…”
Section: Terahertz Optical Hall Effect (Thz-ohe)supporting
confidence: 90%
“…The observed difference could be attributed to a penetration of the 2DEG wavefunction into the AlGaN barrier layer that was shown to be strongly affected by temperature [55] and it is further discussed in Ref. [59].…”
Section: Terahertz Optical Hall Effect (Thz-ohe)mentioning
confidence: 93%
See 1 more Smart Citation
“…It has been shown that the use of a backside cavity with a highly reflective backside surface can enhance the OHE in HEMT structures and EG, as a result of the formation of Fabri-Pérot modes, within the sample-cavity system [37][38][39]. An optical scheme of the cavity-enhanced (CE)-OHE measurement for a sample containing a transparent substrate and a conductive layer on top is shown in Figure 1.3.…”
Section: Cavity-enhanced Optical Hall Effectmentioning
confidence: 99%
“…3.13). The physical cause of the enhancement is the radiation reflected back in by the magnet surface undergoing further polarization-state changes when passing the magneto-optic birefringent sample constituent [165,166]. THz OHE allows performing an OHE measurements a room temperature and with relatively low-field permanent magnet.…”
Section: Cavity-enhanced and In-situ Cavity-enhanced Thz Optical Hallmentioning
confidence: 99%